Scale-up financing and IPOs: Evidence from three surveys - Antonia Botsari; Kilian Kiefer; Frank Lang; Kristian Pal (European Investment Fund (EIF), 2021)
In light of recent EU policy initiatives such as the Capital Markets Union (CMU) action plan, this working paper provides unique insights from Venture Capital (VC) general partners/management companies, Private Equity Mid-Market (PE MM) managers and Business Angels (BA). Specifically, based on the first 2020 waves of the EIF VC, PE MM and BA Surveys, the report focuses on generating insights around three main topics of SME financing: Scale-up financing, Exit environment & Initial Public Offerings (IPOs) and policy-related implications of the above. The study attempts to piece together evidence from the three surveys, provides market insights from respondents in light of recent policy initiatives, and serves as an informative instrument to policy-makers and practitioners.
Keywords: 330; Mittelstandsfinanzierung; Unternehmenswachstum; Private Equity; Börsengang; KMU; Westeuropa